Boron isotopes fractionation and its application progress in groundwater research - Chenbo LEI; Huaming GUO; Shiping XING (Shuiwen dizhi gongcheng dizhi)
Boron (B) is ubiquitous in natural water bodies and rocks. Because of the large relative mass difference between the two stable isotopes of B, 10B and 11B, the B isotopes are susceptible to significant fractionation. Groundwater typically exhibits various δ11B in different hydrogeological environments. The composition and variation of B isotope in groundwater are of great significance to understanding hydrogeochemical processes and the rational development of groundwater resources. Based on the introduction of the principle of B isotope fractionation, this review summarizes the effects of hydrogeochemical processes such as adsorption/coprecipitation, desorption, weathering, and evaporation on groundwater δ11B values. The article systematically present the studies on applying B isotope technique to address hot academic issues. Since the δ11B values of contaminants and seawater often differ significantly from groundwater background values, B isotopes can be utilized to trace both groundwater contamination and seawater intrusion. Differences in the δ11B values of distinct minerals and weathering conditions have a significant impact on the δ11B values of groundwater. Therefore, B isotopes are useful in reflecting the weathering characteristics of minerals and identifying the process of interaction between the geothermal water and the surrounding rocks. B isotopes can also be utilized to trace hydrogeochemical processes associated with the enrichment of fluoride and arsenic, thereby enhancing the knowledge of the formation mechanism of high fluoride and arsenic groundwater. The future studies on groundwater B isotopes should focus on: (1) Supplementing B-isotope techniques with water chemistry and other isotope techniques to quantify contributions of different hydrogeochemical processes to of the specific solute transformation. (2) Long-term monitoring of B isotopes in areas with high B geothermal water and natural inferior groundwater to determine B endmembers in different conditions and to quantitively assess the negative impact of hazardous components on environment. The solution of these scientific issues is not only conducive to promoting the further development of B isotopes in groundwater studies, but also beneficial to improving the systematical understanding of the enrichment mechanism of groundwater hazardous components.